Relationship of erythrocyte adrenoreactivity with their quantitative and qualitative characteristics as a method for assessing the rheological properties of blood in athletes - A. Z. Dautova; E. E. Isaeva; V. G. Shamratova (National Electronic Information Consortium (NEICON), 2021)
Objective of the study: prediction of the rheological properties of blood in young men with different levels of motor activity (MA) by assessing the relationship between the adrenergic reactivity of erythrocytes (ARE) with their quantitative and qualitative parameters.Materials and methods: the study involved young men with a low (41 people) and a high level of physical activity (athletes - 20 people), aged 21-23 years. In all subjects, the total, individual characteristics of erythrocytes and ARE were determined. ERS was assessed by the change in the erythrocyte sedimentation rate (ESR) under the influence of adrenaline in vitro at final concentrations of 10-5; 10-6; 10-7; 10-8; 10-9; 10-11; 10-13 g/ml venous blood. According to the nature of the observed effect, in accordance with the direction of ESR shifts, 3 types of ARE were distinguished: increased ESR in the presence of adrenaline - aggregative (Ar, type 1); no changes - areactive (Ap, type 2); decreased ESR - antiaggregatory (AnAg, type 3).Results: in athletes, inverse correlations of the ARE types were established when exposed to stress concentrations of adrenaline (SCA) (above 10-8 g/ml) with the hemoglobin level (r = -0.59, p = 0.008), the average hemoglobin content in the erythrocyte (r = -0.55, p = 0.016), when exposed to physiological concentrations of adrenaline (PCA) (10-9 g/ml and below) - with the corpuscular volume of erythrocytes (r = -0.51, p = 0.029). In young men with a low level of MA, an inverse correlation was found between the minimum ARE values and the number of erythrocytes (r = -0.36, p = 0.01), and the maximum - with the average concentration of hemoglobin in the cell (r = 0.54, p = 0.04).Conclusion: in young men leading a sedentary lifestyle, the tendency of erythrocytes to aggregate under the influence of adrenaline increases with an increase in their number and intracellular viscosity. In athletes, the predominance of the antiaggregatory type of ARE, and, consequently, more stable rheological properties of erythrocytes and an improvement in microcirculation, are facilitated by a decrease in the size of erythrocytes and an average saturation of cells with hemoglobin.